The dysregulated podocyte phenotype A novel concept in the pathogenesis of collapsing idiopathic focal segmental glomerulosclerosis and HIV-associated nephropathy - Barisoni, Laura; Kriz, Wilhelm; Mundel, Peter; D'Agati, Vivette (Journal of the American Society of Nephrology, 1999)
Abstract. Podocytes are highly differentiated, postmitotic cells, whose function is largely based on their complex cytoarchitecture. The differentiation of podocytes coincides with progressive expression of maturity markers, including WT-1, CALLA, C3b receptor, GLEPP-1, podocalyxin, and synaptopodin. In collapsing forms of focal segmental glomerulosclerosis (FSGS), including idiopathic FSGS and HIV-associated nephropathy, podocytes undergo characteristic, irreversible ultrastructural changes. This study analyzes the expression pattern of the above differentiation markers and of the proliferation marker Ki-67 in collapsing idiopathic FSGS and HIV-associated nephropathy compared with minimal change disease, membranous glomerulopathy, as well as normal adult and fetal human kidney. In minimal change disease and membranous glomerulopathy, all mature podocyte markers were retained at normal levels despite severe proteinuria and foot process fusion; no cell proliferation was observed. In contrast, in collapsing idiopathic FSGS and HIV-associated nephropathy, there was disappearance of all markers from all collapsed glomeruli and of synaptopodin from 16% of noncollapsed glomeruli. This phenotypic dysregulation of podocytes was associated with cell proliferation in both diseases. It is concluded that the loss of specific podocyte markers defines a novel dysregulated podocyte phenotype and suggests a common pathomechanism in collapsing FSGS, whether idiopathic or HIV-associated.
Gesehen am 08.09.2017